Observations of deep-sea fishes and mobile scavengers from the abyssal DISCOL experimental mining area - J. C. Drazen; A. B. Leitner; S. Morningstar; Y. Marcon; Y. Marcon; J. Greinert; A. Purser (Biogeosciences, 2019)
Industrial interest in deep-sea mineral extraction began decades ago, and today it is at an all-time high, accelerated by global demand for metals. Several seafloor ecosystem disturbance experiments began in the 1970s, including the Disturbance and Recolonization experiment (DISCOL) conducted in the Peru Basin in 1989. A large seafloor disturbance was created by repeatedly ploughing the seafloor over an area of ∼10.8 km2. Though a number of studies in abyssal mining regions have evaluated megafaunal biodiversity and ecosystem responses, few have included quantitative and detailed data on fishes or scavengers despite their ecological importance as top predators. We used towed camera transects (1989–1996, 2015) and baited camera data (1989–1992) to evaluate the fish community at the DISCOL site. The abyssal fish community included 16 taxa and was dominated by Ipnops meadi. Fish density was lower in ploughed habitat at 6 months and 3 years following disturbance but thereafter increased over time. Twenty-six years after disturbance there were no differences in overall total fish densities between reference and experimental areas, but the dominant fish, I. meadi, still exhibited much lower densities in ploughed habitat, likely avoiding these areas and suggesting that the fish community remains affected after decades. At the scale of industrial mining, these results could translate to population-level effects. The scavenging community was dominated by eelpouts (Pachycara spp.), hermit crabs (Probeebei mirabilis) and shrimp. The large contribution of hermit crabs appears to be unique amongst abyssal scavenger studies worldwide. The abyssal fish community at DISCOL was similar to that in the more northerly Clarion–Clipperton Zone (CCZ), though some species have only been observed at DISCOL thus far. Also, further species-level identifications are required to refine this assessment. Additional studies across the polymetallic nodule provinces of the Pacific are required to further evaluate the environmental drivers of fish density, diversity and species biogeographies. This information will be important for the development of appropriate management plans aimed at minimizing human impact from deep-sea mining.